Model Gamifikasi pada Aplikasi Smart City sebagai Solusi Pemerintah untuk Meningkatkan Partisipasi Warga - Winona Almira; Wiguna Alodia (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
its implementation, a smart city needs collaboration between government, people, and technology. From those elements, the human factor is the important thing that determines the success of a Smart city. However, in fact, the percentage of Indonesian citizens accessing government-owned sites and applications is still very low, less than 15%. This study aims to provide recommendations for a more interesting Smart City application design through gamification concept. In this study, a qualitative approach with Six Sigma method was conducted on millennial respondents in several major cities in Indonesia. From the study results, 87% of users feel more interested in the modified application. This innovation is expected to lead to increased citizen involvement. This innovation will not only improve citizen participation but also can be an effective solution to improve the quality of citizens to become Smart People, as initial capital in building Smart Economy.